Race and Sport : The Struggle for Equality on and off the Field - Ross, Charles Kenyatta, 1964-; Brooks, Scott (Book collections on Project MUSE., 2004)
"Even before the desegregation of the military and public education and before blacks had full legal access to voting, racial barriers had begun to fall in American sports. This collection of essays shows that for many African Americans it was the world of athletics that first opened an avenue to equality and democratic involvement." "Race and Sport showcases African Americans as key figures making football, baseball, basketball, and boxing internationally popular, though inequalities still exist today." "Although each of these essays explores a different facet of sports in America, together they comprise an analytical examination of African American society's tumultuous struggle for full participation both on and off the athletic field."--Jacket.